Social and practical representations in pneumonia associated to ventilation mechanics - Giovane Mendieta I; Amparo E. Cristancho M (Universidad de Antioquia, 2009)
Objective: To identify the practice and social representations of the respiratory therapists, on the strategies of prevention of pneumonia associated to mechanical ventilation, of the unit intensive care of the Kennedy Hospital. Methodology:Qualitative inquiry, descriptive and explanatory character, the population, respiratorys therapist of the unit's intensives cares, with a sample of captive type for convenience, conformed by seventeen respiratorys therapists who were applied a semistructured interview, applying the content analysis technique for their study. Results: Practices and social representations, are given around the patient, and therefore avoid prolonged mechanical ventilation, the suction procedure should be carried out by means of aseptic technique, on the other and, the strict execution of handling protocols of airway; as long as it should be norm for the whole personnel, hand washing. Conclusions:it is observed the strategies of prevention are influenced by the theoretical references, however, these actors don't know the full prevention strategies, likewise the represented practices are related with the prevention through asepsis transmission of pathogens, and has an effect on the construction of social representations and therefore the knowledge of new practices will change the structure of representation.